Liechtenstein : Anti-Money Laundering and Combating the Financing of Terrorism-Technical Note. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Note evaluates the state of Anti-Money Laundering and Combating the Financing of Terrorism in Liechtenstein. Liechtenstein has made significant steps and achieved considerable progress since the last mutual evaluation, particularly in bringing its legal framework more closely in line with the Financial Action Task Force recommendations, consolidating an overall robust institutional framework for combating money laundering and terrorist financing and moving toward greater transparency. Domestic cooperation is robust, and key stakeholders enjoy the trust of the financial and nonfinancial sectors. However, effective implementation is uneven and not always optimal. Liechtenstein's proactive use of the in rem regime of confiscation of criminal proceeds has proven to be quite effective.